The rise of motivational information systems: A review of gamification research - Koivisto Jonna; Hamari Juho (Elsevier Ltd, 2022)
Today, our reality and lives are increasingly game-like, not only because games have become a pervasive part of our lives, but also because activities, systems and services are increasingly gamified. Gamification refers to designing information systems to afford similar experiences and motivations as games do, and consequently, attempting to affect user behavior. In recent years, popularity of gamification has skyrocketed and manifested in growing numbers of gamified applications, as well as a rapidly increasing amount of research. However, this vein of research has mainly advanced without an agenda, theoretical guidance or a clear picture of the field.
To make the picture more coherent, we provide a comprehensive review of the gamification research (N = 819 studies) and analyze the research models and results in empirical studies on gamification. While the results in general lean towards positive findings about the effectiveness of gamification, the amount of mixed results is remarkable. Furthermore, education, health and crowdsourcing as well as points, badges and leaderboards persist as the most common contexts and ways of implementing gamification. Concurrently, gamification research still lacks coherence in research models, and a consistency in the variables and theoretical foundations. As a final contribution of the review, we provide a comprehensive discussion, consisting of 15 future research trajectories, on future agenda for the growing vein of literature on gamification and gameful systems within the information system science field.